Testing for effective market supervision of New Zealand banks - McIntyre, M.L.; Tripe, David; Zhuang, Xiaojie (Jeff) (Journal of Financial Stability, 2009)
There is a considerable amount of research that seeks to determine the extent to which retail market participants exert market discipline on banks either through the price approach (the correlation of price to risk), or the quantity approach (the movement of funds in response to changes in risk). In this paper we propose and implement a third approach: the retail market conditions approach. We seek to determine if the prerequisites for the exertion of effective market discipline by stakeholder monitors, as set out in Llewellyn and Mayes (2003. The role of market discipline in handling problem banks. Bank of Finland Discussion Papers. extlesshttp://www.bof.fi/eng/7_tutkimus/index.stm extgreater (retrieved 13.04.04)), prevail by directly examining conditions that prevail among retail market participants. We find little evidence to support the proposition that they are being met among New Zealand retail depositors.